Mesenchymal stem cells in the treatment of spinal cord injury: Mechanisms, current advances and future challenges - Xia, Yuanliang; Zhu, Jianshu; Yang, Ruohan; Wang, Hengyi; Li, Yuehong; Fu, Changfeng (Frontiers in Immunology, 2023)
Spinal cord injury (SCI) has considerable impact on patient physical, mental, and financial health. Secondary SCI is associated with inflammation, vascular destruction, and subsequent permanent damage to the nervous system. Mesenchymal stem cells (MSCs) have anti-inflammatory properties, promoting vascular regeneration and the release neuro-nutrients, and are a promising strategy for the treatment of SCI. Preclinical studies have shown that MSCs promote sensory and motor function recovery in rats. In clinical trials, MSCs have been reported to improve the American Spinal Injury Association (ASIA) sensory and motor scores. However, the effectiveness of MSCs in treating patients with SCI remains controversial. MSCs promote tumorigenesis and ensuring the survival of MSCs in the hostile environment of SCI is challenging. In this article we examine the evidence on the pathophysiological changes occurring after SCI. We then review the underlying mechanisms of MSCs in the treatment of SCI and summarize the potential application of MSCs in clinical practice. Finally, we highlight the challenges surrounding the use of MSCs in the treatment of SCI and discuss future applications.